(untitled) (Gaceta Técnica, 2020)
The impact that the COVID-19 pandemic has had on our regular activities is cause for reflection. Those of us who work in educational and research environments have been directly affected by a situation never before foreseen, testing the adaptation capacities to continue participating in the training process of students under the quality criteria expected in university education. Undoubtedly, an exhaustive analysis of the situation would involve knowing the experiences of the student sector and other sectors that make life within the university, it is not intended in these lines to make such an analysis, but rather to expose some ideas of how it has been the practical experience from the perspective of a teacher.